Closantel nano-encapsulated polyvinyl alcohol (PVA) solutions. (3rd July 2016) - Vega, Abraham Faustino; Medina-Torres, Luis; Calderas, Fausto; Gracia-Mora, Jesus; Bernad-Bernad, MaJosefa
Abstract: The influence of closantel on the rheological and physicochemical properties (particle size and by UV–Vis absorption spectroscopy) of PVA aqueous solutions is studied here. About 1% PVA aqueous solutions were prepared by varying the closantel content. The increase of closantel content led to a reduction in the particle size of final solutions. All the solutions were buffered at pH 7.4 and exhibited shear-thinning behavior. Furthermore, in oscillatory flow, a "solid-like" type behavior was observed for the sample containing 30 μg/mL closantel. Indicating a strong interaction between the dispersed and continuous phases and evidencing an interconnected network between the nanoparticle and PVA, this sample also showed the highest shear viscosity and higher shear thinning slope, indicating a more intrincate structure disrupted by shear. In conclusion, PVA interacts with closantel in aqueous solution and the critical concentration for closantel encapsulation by PVA was about 30 μg/mL; above this concentration, the average particle size decreased notoriously which was associated to closantel interacting with the surface of the PVA aggregates and thus avoiding to some extent direct polymer–polymer interaction.